THE NECCESITY OF VISUAL CULTURE TRAINING TO DEVELOP AESTHETIC PERCEPTION ON INDIVIDUALS WHO TAKES ART TRAINING - Selma KARAAHMET BALCI (Fırat University, 2019)
Visual culture includes various fields including; television, sculpture, photography, films, oil paintings, gardens, buildings, hand crafts, toys, advertisements, jewelry, maps, web pages, city landscapes and so on. Therefore, visual culture, is a human experience that has never been (Mirzoeff, 1999) and increasing in a visual and visualized way and is comprehensive respectably. According to Barnard (2002), everything that has been given a functional, communicative and/or an aesthetic apprehension, that is man-made, produced or interpreted is included in the definition of visual culture. According to the pioneer advocate of visual culture Paul Duncum (2002) meaning in today's world is produced in an interactive mean such as visual areas, visual and popular objects, music, sound effects, and pictures and so on. As well as looking at popular elements, the way we look at things is important too. It is undoubtedly more important to look at these objects for an in